Glucose abnormalities in infants with birth asphyxia are associated with later neurological diagnoses - Viitaharju, Niina; Parikka, Vilhelmiina; Löyttyniemi, Eliisa; Singh, Bishwesvar; Helenius, Kjell (Elsevier, 2026)
Objective
To investigate the association between early glycemic profile and neurological outcome in neonates with birth asphyxia.
Study design
Retrospective single-center study on infants born ≥36 weeks gestational age with an ICD-10 diagnosis of birth asphyxia and/or hypoxic-ischemic encephalopathy, using early (<72 h) glucose values and clinical follow-up data extracted from medical records. Outcomes: death or any ICD-10 diagnoses indicating neurodevelopmental disorders (NDD; psychiatric, epileptical, paralytical, visual or hearing disorders) and individual diagnostic classes. Estimates were adjusted for infant sex, delivery mode and therapeutic hypothermia.
Results
Among 272 neonates, 44 infants received therapeutic hypothermia and 228 infants did not. In multivariate analyses of all infants, the association was significant between glucose <2.6 mmol/l and hearing disorders (aOR = 6.7, 95%CI 1.2–37.3). Glucose >8.3 mmol/l was significantly associated with cerebral palsy (OR = 4.5, 95%Cl 1.2–16.4) and hearing disorders (OR = 6.1, 95%Cl 1.2–29.7). In univariate analyses of the 228 infants who did not receive therapeutic hypothermia, both hypoglycemia and hyperglycemia were associated with cerebral palsy: glucose <2.6 mmol/l: OR 5.63 (1.1–29.7) and >8.3 mmol/l OR 8.83 (1.88–41.47); epilepsy: glucose <1.6 mmol/l: OR 12.2 (1.6–91.9) and >8.3 mmol/l 19.4 (2.0–192.6); and hearing disorders: glucose<1.6 mmol/l OR 8.1 (1.3–51.7) and >8.3 mmol/l OR 9.7 (1.6–60.2).
Conclusions
This study suggests that the glycemic profile in neonates with birth asphyxia during the first 72 h is associated with neurodevelopmental disorders. Further research is needed to verify these findings and investigate if neurological outcome could be improved by rigorous glycemic control.